Target setting in the general combined-oriented CCR model using an interactive MOLP method - Hosseinzadeh Lotfi, F.; Jahanshahloo, G.R.; Ebrahimnejad, A.; Soltanifar, M.; Mansourzadeh, S.M. (Journal of computational and applied mathematics, 2010)
The traditional data envelopment analysis (DEA) model does not include a decision maker’s (DM) preference structure while measuring relative efficiency, with no or minimal input from the DM. To incorporate DM’s preference information in DEA, various techniques have been proposed. An interesting method to incorporate preference information, without necessary prior judgment, is the use of an interactive decision making technique that encompasses both DEA and multi-objective linear programming (MOLP). In this paper, we will use Zionts–Wallenius (Z–W) method to reflecting the DM’s preferences in the process of assessing efficiency in the general combined-oriented CCR model. A case study will conducted to illustrate how combined-oriented efficiency analysis can be conducted using the MOLP method.